Understanding women’s suffering and psychological well-being: exploring biopsychosocial factors in mothers of children with ADHD – a case study - Angeline, Jonah; Rathnasabapathy, Maya (Frontiers in Public Health, 2023)
Overview Parents play a dynamic part in child development. Mothers have a great responsibility towards the upbringing child. Previous research has demonstrated that parenting stress levels are high among Parents of children with attention deficit hyperactivity disorder (ADHD). Aim Parenting stress affects the psychological well-being of the mother. It is necessary to identify the factors that affect psychological well-being based on Biopsychosocial factors, including biological, psychological, and social factors. Methodology An in-depth case study was conducted with the mother of a 7-year-old child diagnosed with attention deficit hyperactivity disorder. Results The mother lacks self-efficacy and low perceived social support in. Equipping themselves and building up the knowledge on handling the child and training the child with the developmental disorder increase parenting self-efficacy. Support from family, partner, and society will help them strengthen themselves and may have high psychological support.